Role of fluid density on quartz wettability - Pan, B.; Li, Y.; Xie, L.; Wang, X.; He, Q.; Li, Y.; Hejazi, S.; Iglauer, Stefan (Elsevier, 2019)
© 2018 Elsevier B.V. Hydrocarbon recovery and reserves estimation largely depend upon the hydrocarbon-water-mineral wettability. However, wettability is a complex parameter and experimental measurements are still open to large uncertainty. We thus demonstrate here that quartz wettability correlates with the density of the non-aqueous fluid, e.g. oil, CO2, N2, etc. – which can be in a liquid, gaseous or supercritical form. This insight significantly simplifies wettability assessments, thus enhancing fundamental understanding of wettability and the related fluid dynamics in siliciclastic hydrocarbon reservoirs. Furthermore, this observed correlation may promote hydrocarbon recovery and reserves prediction in siliciclastic reservoirs.